Variable temperature X-ray diffraction and high field EPR study of phase transition in multiferroic mixed ammonium peroxychromates, Rb1.36 (NH4)1.64Cr(O2)4. (November 2018) - Samantaray, Raghabendra; Zhou, Haidong
Graphical abstract: Highlights: Pseudo-Octahedral site symmetry for NH4 + ions at distinct cation site alters the phase transition behavior. The reorientational motion of NH4 + ions depends on its nearest neighbor. The dynamics of NH4 + ions tune the NH⋯O bonding pattern. Abstract: Two cation sites in a unit cell with varying cation (NH4 + ) symmetry are rare, and Rb1.36 (NH4 )1.64 Cr(O2 )4 is one such compound with distinct cation sites. We report a systematic X-ray diffraction study using both single crystals and powder samples of Rb1.36 (NH4 )1.64 Cr(O2 )4, changes in the lattice parameters and symmetry as a function of temperature at a wide range (10–300 K). Pseudo octahedral NH4 + ions at cation sites, N2, are involved in NH⋯O hydrogen bond to yield a continuous second order phase transition in Rb1.36 (NH4 )1.64 Cr(O2 )4 in contrast to a first order step like irregular pattern in its parent compound (NH4 )3 Cr(O2 )4 . High field EPR studies of Cr 5+ at a temperature range 10–300 K revealed a distortion in Cr(O2 )4 groups in the plane (001) suggesting strong NH⋯O hydrogen bonding between (NH4 ) ions and Cr (O2 )4 groups.